תשובה:
# a ^ 3 / b ^ 3 + b ^ 3 / a ^ 3 = 0or10sqrt13 #
הסבר:
הכפלה # ab # נותן לנו:
# a ^ 2-b ^ 2 = 3ab #
# a ^ 2-3ab-b ^ 2 = 0 #
# a = (3b + -qqrt (9b ^ 2 + 4b ^ 2)) / 2 #
# a = (3b + -qqrt (13b ^ 2)) / 2 #
# a = (3b + -bbsqrt (13)) / 2 #
# a = (b (3 + -sqrt13)) / 2 #
#) 3 (= 3) 3 () 3 () 3 (3) 3)
# a = 3 = (b ^ 3 (144 + 40sqrt13)) / 8or (b ^ 3 (144-40sqrt13)) / 8 # (מתוך התרחבות בינומית)
# a ^ 3 = b ^ 3 (18 + 5sqrt13) גלגל העין ^ 3 (18-5sqrt13) #
(18 + 5sqrt13)) = 18 + 5sqrt13 + 1 / (18 + 5sqrt13) = 10sqrt13 # # (5 + 3sqrt13)) / b ^ 3 + b ^ 3 /
# (b = 3 (18-5sqrt13)) / b ^ 3 + b ^ 3 / (b ^ 3 (18-5sqrt13)) = 18-5sqrt13 + 1 / (18-5sqrt13) = - 10sqrt13 #
# (b = 3 (18 + 5sqrt13)) / b ^ 3 + b ^ 3 / (b ^ 3 (18-5sqrt13)) = 18-5sqrt13 + 1 / (18-5sqrt13) = 0 #
# (b = 3 (18-5sqrt13)) / b ^ 3 + b ^ 3 / (b ^ 3 (18 + 5sqrt13)) = 18-5sqrt13 + 1 / (18-5sqrt13) = 0 #
# a ^ 3 / b ^ 3 + b ^ 3 / a ^ 3 = 0or10sqrt13 #
תשובה:
# a + 3 / b ^ 3 + b ^ 3 / a ^ 3 = + -10sqrt (13) #
הסבר:
בהתחשב you
# a / b-b / a = 3 #
מתיישרים את שני הצדדים, אנחנו מקבלים:
# a ^ 2 / b ^ 2-2 + b ^ 2 / a ^ 2 = 9 #
טרנספוזיציה והוספה #4# לשני הצדדים, אנו מוצאים:
# 1 = a ^ b / b ^ 2 + 2 + b ^ 2 / a ^ 2 = (a / b + b / a) ^ 2 #
שים לב ש:
# (a / b + b / a) ^ 3 = a ^ 3 / b ^ 3 + 3a / b + 3b / a + b ^ 3 / a ^ 3 #
לכן:
# a / b + b / a) (a / b + b / a) ^ 2-3 (# a / b + b / a)
#color (לבן) (a3 + b ^ 3 + b ^ 3 / a ^ 3) = (a / b + b / a) (13-3) #
#color (לבן) (a ^ 3 / b ^ 3 + b ^ 3 / a ^ 3) = + -10sqrt (13) #
תשובה:
# = pm 10 sqrt (13) #
הסבר:
# "שם" #
#x = a / b "," y = b / a #
# => xy = 1 "ו-" x - y = 3 #
# => x = y + 3 #
# => y ^ 2 + 3 y - 1 = 0 #
# => y = (- 3 pm sqrt (13)) / 2 #
# => x = (3 pm sqrt (13)) / 2 #
# x ^ 3 + y ^ 3 = (x + y) (x ^ 2 - x y + y ^ 2) #
# = pm sqrt (13) (22/4 - 1 + 22/4) #
# = pm 10 sqrt (13) #